Treasury of Traditional Tales Illustrated by Rene Clocke - Cloke, Rene
This collection of ten timeless fairy tales, beautifully illustrated by Rene Cloke, contains: Pinocchio Cinderella Goldilocks Jack and the Beanstalk Little Red Riding Hood The Adventures of Tom Thumb Aladdin and His Wonderful Lamp Snow White and the Seven Dwarfs The Ugly Duckling Puss in Boots.
Keywords: English Fiction